2021
DOI: 10.1111/trf.16704
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness and budget impact of whole blood pathogen reduction in Ghana

Abstract: Background: Despite the promise of pathogen reduction for reducing transfusion-associated adverse events in sub-Saharan Africa, no healtheconomic assessment is publicly available.Study Design and Methods: We developed a mathematical risk reduction model to estimate the impact of nationwide whole blood pathogen reduction in Ghana on the incidence of six infectious and one non-infectious transfusion-associated adverse events. We estimated the lifetime direct healthcare costs and disability-adjusted life years lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Of these, 36 studies were included in our review. In total, 22 economic evaluations were included [ 21 40 ]; fifteen had the outcome framed in DALYs [ 21 34 , 41 ], and seven had the outcome framed in QALYs [ 35 40 , 42 ]. Two primary studies were identified after hand-searching reference lists [ 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 36 studies were included in our review. In total, 22 economic evaluations were included [ 21 40 ]; fifteen had the outcome framed in DALYs [ 21 34 , 41 ], and seven had the outcome framed in QALYs [ 35 40 , 42 ]. Two primary studies were identified after hand-searching reference lists [ 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table S 11 summarises the key characteristics of the 36 studies reviewed. For the 22 economic evaluations, two studies were from low-income countries [ 21 , 27 ], three from lower-middle-income countries [ 32 , 33 , 41 ], three from upper-middle-income countries [ 22 , 29 , 31 ], eight from high-income countries [ 23 , 35 40 , 42 ], and six from a mixture of countries [ 24 – 26 , 28 , 30 , 34 ]. Fifteen studies (68%) reported the cost-effectiveness of antenatal screening for syphilis [ 21 , 22 , 24 34 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations